An Exploration the Risk of Cardiovascular Disease in HIV-Positive Persons in Indonesia using Heart Rate Variability - Linlin Lindayani; Irma Darmawati; Heni Purnama; Pujowati Pujowati; Taryudi Taryudi (Faculty of Nursing Universitas Padjadjaran, 2019)
Cardiovascular disease is the highest cause of death in HIV patients compared to the general population. The number of HIV patients suffering from cardiovascular disease is almost twice as high as patients who are not HIV-positive.The purpose of this study was to identify the risk of cardivascular disease in patients with HIV using ECG short term. This study was used a descriptive comparative to patients with HIV and healthy people as controls in West Java. The inclusion criteria are patients with HIV over the age of 30 years. The exclusion criteria were people with HIV diagnosed with heart disease or being treated for the heart disease. While the inclusion criteria for healthy people as controls are over 30 years of age, do not suffer from cardivascular disease or under treatment of cardiovascular disease. The measurement of heart rate variability is carried out in a supine position in a quiet temperature-controlled room (25-270 C), a 5-minute electrocardiograph (ECG) is recorded using lead II. Differences of heart rate variability indicator were measure using man-whitney test. A total of 20 patients with HIV and 20 healthy people recruited using convinience sampling. The majority of people with HIV were male and aged range between 27 to 51 years old. The results of heart rate variability based on time domain analysis showed that the means normal to normal (NN) was significantly lower in HIV patients compared to controls (978 vs ?? vs 902 ms; p<0.05). No differences were found between groups regarding Standard deviation of NN (SDNN), Square root of the mean squared difference of successive NN-intervals (RMSSD) and Percent of differences between adjacent NN intervals greater than 50 ms (pNN50). This study presence of autonomic dysfunction as showed in heart rate variability indicator in a group of HIV compared to the healthy group. Eearly identification of the risk of CVD is important and may inform the implementation of preventive measure by identification of high-risk people who may be candidate for intervention.